2015
DOI: 10.1371/journal.pone.0128377
|View full text |Cite
|
Sign up to set email alerts
|

Association of Climatic Variability, Vector Population and Malarial Disease in District of Visakhapatnam, India: A Modeling and Prediction Analysis

Abstract: BackgroundMalarial incidence, severity, dynamics and distribution of malaria are strongly determined by climatic factors, i.e., temperature, precipitation, and relative humidity. The objectives of the current study were to analyse and model the relationships among climate, vector and malaria disease in district of Visakhapatnam, India to understand malaria transmission mechanism (MTM).MethodologyEpidemiological, vector and climate data were analysed for the years 2005 to 2011 in Visakhapatnam to understand the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…Based on the results, it can be concluded that relative humidity and temperature showed a strong association with malaria incidence, which is consistent with the study by Srimath-Tirumula [56],…”
Section: Maysupporting
confidence: 91%
“…Based on the results, it can be concluded that relative humidity and temperature showed a strong association with malaria incidence, which is consistent with the study by Srimath-Tirumula [56],…”
Section: Maysupporting
confidence: 91%
“…This climatic-vector interaction is common in Culex , Aedes , and Anopheles mosquitoes, for example, vector population dynamics are strongly associated with climatic conditions, winter diapause or refuge, and water availability affecting mosquito development [ 46 – 49 ]. This seasonality in vector abundance leads to seasonality of vector-borne infectious diseases [ 41 , 42 , 45 , 49 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The distribution and abundance of vectors is determined by the interplay of three factors: suitable climatic conditions, habitat for development, and the availability of hosts for food. These factors are not independent, since changes in climate not only directly affect the conditions for vector development but also indirectly alter vegetation cover and the movement of the hosts (Jones et al , Reisen et al , Mills et al , Moore and Messina , Srimath‐Tirumula‐Peddinti et al ). Of the different aspects of climate, temperature has been shown to influence the growth and proliferation of trypanosomes within the tsetse fly (Walshe et al ).…”
Section: Introductionmentioning
confidence: 99%